Work Experience as a Moderating Variable of the Influence of Intelligence on the Performance of Malang Government Employees - Tri Yulianto; Siswanto Siswanto; Masyhuri Masyhuri (AL-QARDH, 2021)
This study aims to see the effect of intellectual intelligence and emotional intelligence on employee performance with experience as a moderating variable. This research was conducted at the Public Works Department of Malang City. The type of research used is a quantitative approach research model using data in the form of numbers. The sample used as many as 122 respondents with the technique of taking census research. Two regression tests were carried out; the first was the independent variable test without the moderating variable, the second was carried out on all independent variables and the moderating variable. This study indicates that in the first test simultaneously or partially, all intellectual and emotional intelligence influence employee performance. After being moderated with work experience variables in the second test, intellectual and emotional intelligence variables become insignificant on employee performance. Thus, the moderating variable of work experience is only a moderating predictor variable.